Analysis of Learning Methods in Improving the Quality of Islamic Education at Sirrul Qur'an Islamic Boarding School - Lukman Saefi; M.Maulana Nur Kholis (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to analyze the learning methods at Sirrul Quran Islamic Boarding School and evaluate their effectiveness in shaping students' character and religious understanding. This qualitative research, using a case study approach, found that the tahsin and tahfidz learning process at the pesantren involves six stages: Bin Nadzar, Tahfidz, Talaqqi, Takrir, Tasmi', and Mutqin. The success of this method is measured by the improvement in students' academic performance and motivation, as well as the teachers' ability to manage learning strategies. The study found that out of 15 respondents, 10 students obtained an average score above 80, indicating the effectiveness of the applied learning method. However, the study also identified challenges, namely the limited role of parents in supporting students at home and the difficulty some students face in adapting to learning media. Nevertheless, the teachers' role in guiding and providing inspirational lectures from the Quran proved effective in enhancing students' faith and devotion, which is reflected in their enthusiasm for learning tahsin and tahfidz.